Optimization of Temperature and Time of Microwave Assisted Extraction of Dewandaru Leaves (Eugenia uniflora L.) on Antioxidant Activity and Its Application in Body Scrub - Khoirul Anwar; Gharsina Ghaisani Yumni; Ayu Shabrina; Aulia Septiani Putri; Melani Putri Britama (Jurnal Ilmiah Sains, 2025)
Dewandaru leaves (Eugenia uniflora L.) contain phenolic and flavonoid compounds that function as natural antioxidants. This study aimed to determine the optimal extraction temperature and duration using the Microwave-Assisted Extraction (MAE) method to maximize the antioxidant activity of the ethanolic extract of Dewandaru leaves, and to incorporate the optimized extract into a body scrub formulation. Extractions were carried out at temperatures ranging from 40–80 °C and durations of 10–30 minutes, optimized using Design Expert 13.0. Phytochemical screening and FTIR spectra confirmed the presence of phenolic and flavonoid compounds, indicated by absorption peaks at 3248.4 cm⁻¹ (bonded O–H), 1654.9 cm⁻¹ (conjugated aromatic C=C), and 1112.6–1205.8 cm⁻¹ (phenolic C–O). The IC₅₀ value was used as an indicator of antioxidant activity. The optimal combination was obtained at 63 °C and 30 minutes, yielding 24.794% extract with an IC₅₀ value of 70.325 ppm. The optimized extract was formulated into four variations of body scrub and evaluated for physical parameters such as pH, viscosity, spreadability, and adhesiveness. All formulations exhibited stable characteristics suitable for topical application. These findings indicate that the MAE method is effective for extracting bioactive compounds from Dewandaru leaves and has potential for development as an active ingredient in natural cosmetic preparations. Keywords: Antioxidants;  body scrub; dewandaru; flavonoids